Adaptation, validity and reliability of the modified painDETECT questionnaire for patients with subacromial pain syndrome. - Barbara C Boer; Jolanda Boetje; Martin Stevens; Inge van den Akker-Scheek; Jos J A M van Raay (PLoS ONE, 2019)
BACKGROUND:The identification of a neuropathic component to subacromial pain may lead to different pain management strategies. The purpose of this study was to adapt the Dutch modified painDETECT (mPDQ-NL) Knee, which discriminates between nociceptive and neuropathic pain, to fit patients with subacromial pain syndrome and subsequently assess its validity and reliability. METHODS:The mPDQ-NL Knee was adapted into the mPDQ-NL Shoulder to fit and use for patients with subacromial pain syndrome. The study population consisted of patients suffering from subacromial pain syndrome who were asked to fill in the Dutch mPDQ-NL Shoulder, the self-completed Leeds Assessment of Neuropathic Symptoms and Signs (S-LANSS) and the Disabilities of the Arm, Shoulder and Hand (DASH) to determine construct validity (structural validity, hypotheses testing) of the mPDQ-NL Shoulder. Regarding reliability, internal consistency was determined and the mPDQ-NL Shoulder was assessed a second time with a two-week interval to determine measurement error and reliability. RESULTS:A total of 107 patients were included in the validity analysis and 58 in the reliability analysis. Validity (86% of predefined hypotheses met), internal consistency (Cronbach's alpha 0.8) and reliability (ICC 0.7) of the mPDQ-NL Shoulder were good, however, a systematic bias might be present. CONCLUSION:The mPDQ-NL Shoulder was successfully modified from the mPDQ-NL Knee. This study shows that the mPDQ-NL Shoulder seems to reflect neuropathic-like pain symptoms experienced by patients with SAPS. Whether it may also be used as a tool to record change over time or after treatment has to be further assessed.